Aplicação de métodos quimiométricos para a determinação de constituintes inorgânicos em leite materno por ICP-MS e ICP OES - Rosilene da Silva Nascimento (2008)
The human milk is constituted in the only source of nutrients during the first months of the child's life and consequently, its elementary composition is of fundamental importance for the infantile growth and the correspondent wanted health condition. In this work, we quantified the elements 27Al, 53Cr, 55Mn, 57Fe, 60Ni, 65Cu, 64Zn, 66Zn, 78Se, 82Se,112Cd, 114Cd, 206Pb, 208Pb, 138Ba, 51V, 59Co and 75As by ICP-MS; and by ICP OES, the elements Ca, K, Mg, Na, Cr, Cu, Fe, Mn, Zn, Ba, Al, Cd, Pb, V, Ni, Co and Li, all presents in mature and colostrums human milk. In this study it was also made the verification of the methods of linear regression, OLS (Ordinary Least Square) and (WLS) Weighted Least Square , used to do the calibration of the analytical method, for being this an important stage of the analytical process. The evaluation of the chosen adjustment, it was accomplished using the standardized residues and the 2 red c . We also used the curves of the confidence limits of the adjustment, together with the calibration curve line, and the curves of the prediction limits of the adjustment, for terms a better estimate of possible spurious values (outlier), in other words, values that don't possess the same population of data. We compared several methods to express the detection and quantification limits of the analytical methods, demonstrating the great difficulty that we have when of the choice of these methods, for we have not any standardization of which method to use. The precision of the analyses accomplished by ICPMS, expressed as relative standard deviation (R.S.D.), it was better or equal to 3.4% and for the analyses made by ICP OES, the precision was better or equal to 3.3%. Para to check the accuracy of the methods, studies involving spike and recovery was also used. The recoveriesfor the analyses accomplished by ICP-MS, were in the range of 80.8 110.9% and for the analyses accomplished by ICP OES, were in the range of 83.1 117.3%. The values obtained as by ICP-MS as by ICP OES, compared with the recommended values in the certified reference material, presented agreement amongst themselves, for a confidence level of 95%. With that, we can conclude that the proposed methods are adapted for quantification of the elements analyzed by ICP-MS and by ICP OES, presents in human milk. We also verified that significant difference doesn't exist among the two methods, being possible the determination of the studied metals as by ICP-MS as ICP OES.